PENERAPAN SISTEM PENGELOLAAN DAN PENCATATAN DANA KAS KECIL TERHADAP PENINGKATAN KINERJA OPERASIONAL PADA PT MAKMUR INDO TUNGGAL (STUDI KASUS TAHUN 2023) - Andriani, Desika; Salsabila, Vania Aurellia (Sekolah Tinggi Ilmu Ekonomi Bhakti Pembangunan, 2025)
This research aims to determine the procedures in the petty cash fund management andrecording system, the process flow in the petty cash fund management and recording system,what methods are used in the petty cash fund management and recording system, thedocuments required in the petty cash fund management and recording system , accountingrecords carried out in managing and recording petty cash funds, obstacles in managing andrecording petty cash funds, evaluation in managing and recording petty cash funds towardsimproving operational performance in 2023. Data from conducting field surveys that arerelated to the problem under study . This type of research was carried out to obtain primarydata, consisting of: Observations and interviews. The results show that this system involves afinance department that is responsible for submitting and verifying expenditures, ensuringeach transaction is supported by relevant evidence. Petty cash funds are used for various dailyoperational expenses such as purchasing live shopee and tiktokshop coins, KOL endorsementpayments, and shipping costs for goods. The expenditure application and verification processis carried out carefully to ensure accuracy and relevance to needs.